2023
DOI: 10.1021/acs.langmuir.3c01466
|View full text |Cite
|
Sign up to set email alerts
|

A Curated Graphene Quantum Dot-Porphyrin-Based Photosensitizer for Effective Singlet Oxygen Generation through Energy Transfer

Abstract: Porphyrin-based photosensitizers are proven generators of reactive oxygen species (ROS), such as singlet oxygen, and used as anti-cancer therapeutic agents. However, most of these compounds suffer from potential drawbacks due to limited photostability, hydrophobicity, aggregation propensity, and low cellular uptake. Ultrasmall fluorescent graphene quantum dots (GQDs) have emerged as the next-generation carriers for drugs and have gained reputation in the pharmaceutical domain. Considering the various limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…This not only produces systems with large Stokes shift but also reduces the crosstalk between the excitation and the emission signals of the systems significantly, therefore decreasing the self-quenching of photosensitizers. Sometimes ROS produced from direct excitation of the photosensitizers does not show enough efficacy in PDT, while FRET can significantly enhance it. This is purely a proof of concept where we have mimicked the physiological conditions, and hence, we expect similar results in real application. There should not be a remarkable difference in the parameters in physiology.…”
Section: Introductionmentioning
confidence: 86%
“…This not only produces systems with large Stokes shift but also reduces the crosstalk between the excitation and the emission signals of the systems significantly, therefore decreasing the self-quenching of photosensitizers. Sometimes ROS produced from direct excitation of the photosensitizers does not show enough efficacy in PDT, while FRET can significantly enhance it. This is purely a proof of concept where we have mimicked the physiological conditions, and hence, we expect similar results in real application. There should not be a remarkable difference in the parameters in physiology.…”
Section: Introductionmentioning
confidence: 86%
“…Results of the cytotoxicity test under dark conditions demonstrated that free TNPP led to cytotoxicity in a concentration dependent manner, which was decreased by its conjugation with GQDs. 36…”
Section: Gqds In Cancer Therapymentioning
confidence: 99%
“…Chemotherapy, a systemic cancer treatment, lacks specificity to tumor cells, causing collateral damage to normal cells. In contrast, photodynamic therapy (PDT) stands out as a noninvasive approach with reduced side effects and enhanced selectivity. , The efficacy of PDT depends on the production of reactive oxygen species (ROS) by photosensitizers, which can react directly with biological substrates, leading to toxicity and subsequent tumor cell death . However, its broader application is hindered by limitations, especially the toxicity at higher photosensitizer concentrations in the absence of light. , Recent advancements in amphiphilic polymeric nanomicelle delivery systems have enabled flexible loading of photosensitizers and drugs while overcoming physiological barriers. However, most of the existing systems rely on molecular self-assembly micelles that physically encapsulate drugs and photosensitizers, and these molecules interact strongly to form corresponding aggregates, bringing about the extremely low accumulation of effective loading rate in tumor tissues. , This issue is compounded by poor stability and structure dissociation in complex physiological environments, compromising therapeutic agent enrichment at the tumor sites. , Addressing the challenges of micelle dissociation involves synthesizing amphiphilic dendrimers, star-shaped polymers, and hyperbranched polymer micelles. A particularly promising solution is unimolecular micelles, where each polymer molecule behaves as a micelle, maintaining structural integrity, even in dilute solutions.…”
Section: Introductionmentioning
confidence: 99%